A Study of Green HRM Practices In Manufacturing Companies In Perlis - Runismar, Razali (2020)
The main objective of the study is to find out the green HRM practices in manufacturing companies in Perlis. Specifically, the study examines the relationship between green working environment, employee awareness and green HRM practices. A survey was conducted to collect data from the respondents by using questionnaire. The researcher used convenience sampling for selecting respondents from five manufacturing companies in Perlis. Statistical Packages for Social Science (SPSS) version 22.0 was used to analyze the data. A total of 150 questionnaires were distributed and 123 questionnaires were successfully collected from the respective respondents. The results showed that employee awareness was significantly related to green HRM practices. Therefore, the management or organization should provide training programs or courses for employees especially regarding environmental issues to enhance the awareness towards green HRM practices.